Sunn Hemp - A Cover Crop in Florida - Yuncong Li; Qingren Wang; Waldemar Klassen; Edward A. Hanlon (EDIS, 2009)
Revised! SL-306 (formerly SS-AGR-96), a 4-page illustrated fact sheet by Yuncong Li, Qingren Wang, Waldemar Klassen, and Edward A. Hanlon, Jr., describes this green manure crop that has been grown for centuries in Southeast Asia — origin and distribution, description, uses, production and harvest, and seed production. Includes references. Published by the UF Department of Soil and Water Sciences, August 2009.